5‐Year outcomes after transcatheter aortic valve implantation: Focus on paravalvular leakage assessed by echocardiography and hemodynamic parameters. Issue 5 (18th January 2022) - Schoechlin, Simon; Hein, Manuel; Brennemann, Tim; Eichenlaub, Martin; Schulz, Undine; Jander, Nikolaus; Neumann, Franz‐Josef
Abstract: Objectives: We sought to assess the impact of echocardiographic and hemodynamic grading of paravalvular leakage (PVL) after transcatheter aortic valve implantation (TAVI) on the prediction of 5‐year mortality. PVL after TAVI is known to influence outcome after TAVI. Yet, present available data of long‐term outcomes and especially the comparison of different modalities for measurement of PVL is little. Methods: We performed a retrospective single‐center cohort study and compared the prognostic value of echocardiographic PVL grading as well as the aortic regurgitation index (ARI) pre‐ and post‐TAVI. Univariable and multivariable Cox proportional regression analysis generated hazard ratios for mortality. Results: A total of 464 patients underwent TAVI at our center between August 2012 and Decemebr 2014, with self‐expandable CoreValve (11%) or balloon‐expandable Sapien XT (47.4%) and Sapien 3 (41.6) valves. Overall 5‐year mortality was 52.4% (243/464). Echocardiographic classes of PVL at discharge showed a significant ( p = 0.002) association with 5‐year mortality, mild PVL remained as an independent predictor for 5‐year mortality in multivariable analysis (hazard ratio: 1.642 [95% confidence interval: 1.235–2.182]; p = 0.001). Grades of PVL as assessed during the procedure by ARI (below the previously defined cut‐off of 25) did not show a significant association with 5‐year mortality ( p = 0.417 and p = 0.995, respectively). Conclusions: Even mild PVL assessed by echocardiography was an independent predictor for 5‐year survival, whereas hemodynamic measurements did not help to identify PVLs that are relevant to 5‐year survival.